Maritime Unmanned From Global Hawk to Triton. - Snowden, Ernest (Naval Institute Press, 2021)
Maritime Unmanned recounts the promising beginning, demoralizing setbacks, and ultimate success of the visionaries who championed unmanned aircraft systems (UAS) technology for the U.S. Navy.